Peningkatan Pemahaman Hak Alimentasi terhadap Kelompok Lanjut Usia Melalui Legal Counseling Approach - Waspiah, Waspiah; Rodiyah, Rodiyah; Latifiani, Dian; Arifin, Ridwan; Cahyani, Kartika Fajar; Pertiwi, Adinda Ratna; Widiastuti, Anita Indah; Ayu, Adelia Setya (Jurnal Pengabdian Hukum Indonesia (Indonesian Journal of Legal Community Engagement) JPHI, 2021)
The obligations of children in parental care are clearly regulated, both in Article 46 paragraph 1 of Law Number 1 of 1974 concerning Marriage and Article 321 of the Indonesian Civil Code. These two rules emphasize the obligation of children (mature) to care for and provide for their parents. However, the implementation of this rule is still not uniform. One of the contributing factors, apart from the economic level (poverty) is also the unequal perception and level of education in understanding this right which is still low. This research is a community service program funded by the Universitas Negeri Semarang. This program is located on Kedungkelor Village, Wanureja District, Tegal Regency, Central Java. This program aims to determine the level of change in understanding of the right of alimentation for the elderly group in Kedungkelor Village through the Legal Counseling Approach method. This method is a combination of methods of education, socialization, and legal assistance for residents. This program showed a pattern of significant changes in the level of understanding of the alimentation rights of the elderly. Of the 50 people surveyed showed an increasing trend of understanding. This program includes three important stages, namely: planning, advice, and legal action. In the legal action stage, this program involves the Youth Counseling Information Center (Pusat Informasi Konseling Remaja, PIKR) and the Elderly Health House (Rumah Sehat Lansia, RUSELA) in Kedungkelor Village in maximizing this level of understanding.